Impact of Community Outreach Programs of Taguig City Police Station Community Affairs Development Division: Basis for a Capacity Development Plan - Nebrida, Alan P.; Ojeda, Anthony O. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study will assess the impact of the outreach programs that are implemented by the Community Affairs Development Division (CADD) of the Taguig City Police Station as relates to peace and order, intelligence collection, image of the police, effectiveness at resolution of crimes among many others. Several reasons are cited for conducting studies like the above ones and these include evaluation of the effectiveness of programs and the establishment of areas that require improvements. Information was collected from barangay officials, CADD personnel, and their auxiliary members using a quantitative research design comprised of surveys, interviews, and focus group discussions. It was discovered that outreach benefited the police reputation, intelligence gathered, the ability to solve crimes, in general, the maintenance of public order, through stronger police-community partnerships and raised sentiments of safety. Nevertheless, the shortcoming of the program was also commended just as much as very poor communication between the police and the community members and very few of they in intelligence gathering. In accordance with the query of the effectiveness of the programs, there was no statically significant difference between the categories of the respondents, both showing that programs are helpful. But resources, which have been identified to be challenged in the CADD outreach programs, relate to resource management, diversity of skills, communication with partner agencies, and availability of the venue, allocation of the budget, financial support on constant basis, and inter-agency cooperation to name the few. In this context, the report on 'Partnerships between Law Enforcement and Local CADD Agencies' observes, The CADD outreach programs have greatly reduced the problem in relation to the concerns of both public safety and the relation of the law enforcement agency with the community. There will be improved diversification of skills and competence levels, effective utilization of the resources, good communication means, and proper housing. All this with increased budget allocations, regular financial help and strengthening links with other agents.